Paediatric antimicrobial stewardship and safe prescribing-an assessment of medical staff knowledge and behaviour - Mostaghim M; Snelling T; Katf H; Bajorek B (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objective: Determine baseline knowledge of antimicrobial stewardship, and safe prescribing among junior medical officers, monitor their level of participation in interactive education during protected teaching time and assess day-to-day prescribing behaviours over the subsequent 3-month period. Methods: A voluntary and anonymous survey of all non-consultant level medical officers was conducted with the use of an audience response system during mandatory face-to-face orientation sessions at a tertiary paediatric hospital. Routine prescribing audits monitored compliance with national and locally derived quality use of medicines indicators. Results: Eighty-six percent of medical officers participated by responding to at least one question (171/200). Response rate for individual questions ranged between 31% and 78%. Questions that addressed adverse drug reactions, documentation and monitoring for empiric antibiotics and the error-prone abbreviations IU and U were correctly answered by over 90% of participants. Other non-standard and error-prone abbreviations were less consistently identified. In practice, 68% of patients had complete adverse drug reaction documentation (113/166). Error-prone abbreviations were identified on 5% of audited medication orders (47/976), approximately half included a documented indication and intended dose. Conclusions: Participants demonstrated a good understanding of safe prescribing and antimicrobial stewardship. Audits of prescribing identified potential discrepancies between prescribing knowledge and behaviours.